2018
DOI: 10.1073/pnas.1713936115
|View full text |Cite
|
Sign up to set email alerts
|

Range dynamics of mountain plants decrease with elevation

Abstract: Many studies report that mountain plant species are shifting upward in elevation. However, the majority of these reports focus on shifts of upper limits. Here, we expand the focus and simultaneously analyze changes of both range limits, optima, and abundances of 183 mountain plant species. We therefore resurveyed 1,576 vegetation plots first recorded before 1970 in the European Alps. We found that both range limits and optima shifted upward in elevation, but the most pronounced trend was a mean increase in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
290
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(345 citation statements)
references
References 41 publications
28
290
3
Order By: Relevance
“…This apparent 'thermophilisation' of plant species composition in central Nepal is most likely due the species tracking their climate niche under climate warming. This trend is broadly consistent with the patterns of warmingdriven compositional changes across Asia (e.g., Bai et al 2011;Telwala et al 2013;Agnihotri et al 2017), Europe, and North America (e.g., Grabherr et al 1994;Walther et al 2002;Klanderud & Birks 2003;Walther et al 2005;Felde et al 2012;Gottfried et al 2012;Rumpf et al 2018). …”
Section: Assumptionssupporting
confidence: 80%
See 1 more Smart Citation
“…This apparent 'thermophilisation' of plant species composition in central Nepal is most likely due the species tracking their climate niche under climate warming. This trend is broadly consistent with the patterns of warmingdriven compositional changes across Asia (e.g., Bai et al 2011;Telwala et al 2013;Agnihotri et al 2017), Europe, and North America (e.g., Grabherr et al 1994;Walther et al 2002;Klanderud & Birks 2003;Walther et al 2005;Felde et al 2012;Gottfried et al 2012;Rumpf et al 2018). …”
Section: Assumptionssupporting
confidence: 80%
“…climate warming and land-use change, and accord with the major trends of temperature and land-use driven changes across the mountainous areas of the world (e.g., Lenoir et al 2010b;Bai et al 2011;Gottfried et al 2012;De Frenne et al 2013;Rumpf et al 2018). A closer examination of the evident changes, however, reveals rather different trends in response to the two explanatory factors and some of the patterns are potentially confounded due to interactions between climate change and land-use change.…”
Section: Assumptionsmentioning
confidence: 66%
“…The literature is rife with predictions for future species distributions based on shifting temperature isotherms, and indeed, there is good evidence that many species have already shifted up in latitude or elevation with recent warming (Parmesan and Yohe 2003;Chen et al 2011;Rumpf et al 2018). Similarly, in a survey of plants in the European Alps, Rumpf et al (2018) found that nearly half of the species had at least one range attribute (range center, leading edge, or rear edge) that shifted downslope. For example, Chen et al (2011) found that 22% of the species they examined underwent range shifts in the direction opposite that expected from climatic trends (e.g., downslope in spite of warming).…”
mentioning
confidence: 99%
“…For example, several butterfly species are in decline at the southern edge of their original range (Franco et al 2006). In mountains, many plant species are not anymore found at the lower altitudes of their original range (Rumpf et al 2018). In contrast, climate warming also creates opportunities for range expansion, as plant and animal species favouring warm conditions may colonize areas that previously were too cold.…”
Section: Range Boundaries On the Move: Retractions And Expansionsmentioning
confidence: 99%
“…To avoid local extinction, species either need to adapt to the novel local conditions, or shift their range towards previously unsuitable areas (Berg et al 2010). As a consequence, many organisms have been recorded to expand their range to higher latitudes or altitudes (Parmesan & Yohe 2003;Rumpf et al 2018;Steinbauer et al 2018).…”
Section: Introductionmentioning
confidence: 99%